Modeling atmospheric and oceanic flows insights from laboratory experiments and numerical simulations - Larcher, Thomas von; Williams, Paul D. (Geophysical monograph, 2015)
Provides a broad overview of recent progress in using laboratory experiments and numerical simulations to model atmospheric and oceanic fluid motions. This volume not only surveys novel research topics in laboratory experimentation, but also highlights recent developments in the corresponding computational simulations. As computing power grows exponentially and better numerical codes are developed, the interplay between numerical simulations and laboratory experiments is gaining paramount importance within the scientific community.--Provided by publisher